2021
DOI: 10.14741/ijcet/v.11.5.4
|View full text |Cite
|
Sign up to set email alerts
|

Superiority of Sustainable Ozone Wash Over Conventional Denim Washing Technique

Abstract: Denim jeans need to be wet-processed in order to create a comfortable feel and a versatile look in the end product. The use of Ozone to finish denim jeans offers environmental and economic benefits by reducing rinse periods, water use, and energy consumption. Ozone is a specialized oxidant with a strong oxidation potential and can decolorize textile effluents, and it has a particular affinity for indigo. This paper will demonstrate why Ozone-based denim wash should be recognized as sustainable in different asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…At 82.66%, ozone washing has the highest efficiency in terms of TSS, with nearly 48.83% for BOD. A research article provides similar findings [25]. The particles in water that a filter may catch are called TSS.…”
Section: Sustainability Of Ozone Washing Compared To Conventional Was...mentioning
confidence: 86%
See 1 more Smart Citation
“…At 82.66%, ozone washing has the highest efficiency in terms of TSS, with nearly 48.83% for BOD. A research article provides similar findings [25]. The particles in water that a filter may catch are called TSS.…”
Section: Sustainability Of Ozone Washing Compared To Conventional Was...mentioning
confidence: 86%
“…In conventional denim washing, a large amount of water and chemicals are used, contaminating the water with solid particles and chemical components [14]. On the other hand, it has been shown that ozone washing and laser fading consume less water and chemicals than traditional wash due to the removal of several processes in the whole washing process [25]. Ozone washing eliminates the desizing procedure.…”
Section: Process Of Denim Washing For Different Methodsmentioning
confidence: 99%
“…[256,257] Every day, a vast quantity of pollutants, including waste oil, heavy metal ions, and organic and synthetic dyes, is released into the aquatic ecosystem, causing damage to the environment, animals, and people. [258,259] Solilar-driven interfacial evaporation is a sustainable and effective method for desalination and atmospheric water harvesting, utilizing solar energy. This technique offers a promising solution for freshwater production.…”
Section: Water Evaporation and Treatmentmentioning
confidence: 99%
“…According to the study, treating denim fabrics using ozone particles reduces the processing time for clothing and uses less water and chemicals than traditional finishing techniques. Ozone-based finishing also generates a negligible quantity of effluent due to the low chemical and water usage, making it less harmful to the environment and the effluent treatment plant (ETP) than conventional denim washing (Sarker, 2021). A few environmentally friendly dry-cleaning techniques for clothing include whiskering, hand-sanding, grinding, and destruct effects.…”
Section: Koksal Et Al (2017)mentioning
confidence: 99%